1984
DOI: 10.1002/zaac.19845150819
|View full text |Cite
|
Sign up to set email alerts
|

Zum Modifikationswechsel von SiO2 in Gegenwart von Alkali‐Fluoriden und ‐Silicaten

Abstract: Die Einwirkung von NaF und Na2SiF6 auf SiO2 und Natriumsilicate wurde untersucht. Das zugleich entstehende SiF4 beeinflußt den Reaktionsablauf, wie ein Vergleich der Versuche im offenen und geschlossenen System zeigt. Bei geringem SiF4‐Druck führen Umsetzungen von NaF oder Na2SiF6 mit einigen SiO2‐Modifikationen zu Natriumsilicaten, bei merklichen Drucken von SiF4 zu Cristobalit, Tridymit und auch zu T‐Quarz. Viele Natriumsilicate gehen mit NaF vorzugsweise in Na2SiO3 über. Na6Si8O19 entstand aus Na2SiO3, war … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a closed system, the authors reported no reactions between NaF and SiO 2 . Based on Krug et al [137] results, it appears reasonable to assume that the thermal arrests measured by Sedykh et al in a ''crucible electric furnace'' (which is likely an open system) do not correspond to invariant reactions in the (NaF + SiO 2 ) section, but rather within the (NaF + SiO 2 + Na 2 Si 2 O 5 ) system. Moreover, based on the present assessment, the calculated partial pressure of SiF 4 at the composition of the reported thermogravimetric data (which was supposed to be in mole fraction for the calculation) is 0.3 Pa at 1000 K, 2568.7 Pa at 1200 K and 14771.2 Pa at 1400 K. This shows the tendency of SiF 4 to evaporate, resulting in a shift of the composition of the sample.…”
Section: The (Naf + Sif 4 ) Systemmentioning
confidence: 94%
See 1 more Smart Citation
“…In a closed system, the authors reported no reactions between NaF and SiO 2 . Based on Krug et al [137] results, it appears reasonable to assume that the thermal arrests measured by Sedykh et al in a ''crucible electric furnace'' (which is likely an open system) do not correspond to invariant reactions in the (NaF + SiO 2 ) section, but rather within the (NaF + SiO 2 + Na 2 Si 2 O 5 ) system. Moreover, based on the present assessment, the calculated partial pressure of SiF 4 at the composition of the reported thermogravimetric data (which was supposed to be in mole fraction for the calculation) is 0.3 Pa at 1000 K, 2568.7 Pa at 1200 K and 14771.2 Pa at 1400 K. This shows the tendency of SiF 4 to evaporate, resulting in a shift of the composition of the sample.…”
Section: The (Naf + Sif 4 ) Systemmentioning
confidence: 94%
“…Using high-temperature X-ray analysis, Sedykh et al [136] determined that the first thermal arrest corresponds to a transition from amorphous silica to low-cristobalite, and the second one to a transition to low-quartz. However, Krug et al [137] have shown that, depending on the crystalline form of SiO 2 and the possibility for SiF 4 to escape or not the system, NaF can react partially with SiO 2 to form sodium silicates. Krug et al In an open system, fine crystalline SiO 2 powder reacts with NaF to form Na 2 Si 2 O 5 and Na 2 SiO 3 , but no reaction was observed by Krug et al with amorphous SiO 2 or low-quartz, whereas Na 2 Si 2 O 5 was observed when cristobalite was used.…”
Section: The (Naf + Sif 4 ) Systemmentioning
confidence: 98%